Development of the Proactive Behavior Scale for Mid-Career Nurses: a reliability and validity study - Satomi Koyama; Yumiko Miyoshi; Kimie Takehara (Fujita Medical Journal)
Objectives: This study aimed to assess the reliability and validity of the Proactive Behavior Scale for Mid-Career Nurses, which was designed to measure the proactive behavior of nurses who have worked outside their current employment hospital (mid-career nurses) and who are in the process of organizational socialization. Methods: A mail survey was administered to 875 mid-career nurses using a draft version of the Proactive Behavior Scale. An exploratory factor analysis was conducted on the data, and a Proactive Behavior Scale for Mid-Career Nurses was developed (Survey 1). Additionally, a mail survey was administered to 706 mid-career nurses to examine the reliability and validity of the scale (Survey 2). Results: From the exploratory factor analysis results, three factors and 21 items were extracted. The three factors were (1) positive actions toward self-reliance, (2) positive actions toward reliable nursing practices, and (3) positive actions toward building relationships. The Cronbach’s alpha coefficient for the overall scale was 0.89, Spearman’s rank correlation coefficient for the test-retest method was 0.75, and Pearson’s product–moment correlation coefficient for the external criterion, the Scale of Proactive Behavior in Organizational Socialization for New Graduate Nurses and the Scale of Organizational Resocialization were 0.72 and 0.40, respectively. Conclusions: The Proactive Behavior Scale for Mid-Career Nurses has good reliability and validity.